Continuities and Discontinuities: Antiziganism in Germany and Italy (1900-1938) - Illuzzi, Jennifer (Sociología Histórica, 2020)
In both Germany and Italy before WWI, populations labelled as Gypsies found themselves in a “state of exception” which aimed at their elimination from the nation-state by targeting them with policies emanating from the executive. Both states adhered to the liberal idea of equality before the law, but used the flexibility provided by executive authority to pressure Gypsies to leave the state. After WWI, both Germany and Italy were forced to retain “Gypsies” inside the state as a result of changing geopolitical circumstances. However, in fascist Italy before WWII, executive authorities continued to operate in a “state of exception” and ceased adhering to the rule of law, interning Gypsies in concentration camps and seeking to eliminate them through forced assimilation. In Weimar Germany, legislative policies sought to eliminate Gypsies through bringing them inside of the law. The contradiction between increasingly racialized notion of Gypsy inassimilability and forced assimilation’s inevitable failures certainly laid the groundwork for extreme measures in both places during WWII.